1999
DOI: 10.1109/13.762946
|View full text |Cite
|
Sign up to set email alerts
|

Plagiarism in programming assignments

Abstract: Assessment of programming courses is usually carried out by means of programming assignments. Since it is simple to copy and edit computer programs, however, there will always be a temptation among some students following such courses to copy and modify the work of others. As the number of students in these courses is often high, it can be very difficult to detect this plagiarism. We have developed a package which will allow programming assignments to be submitted on-line, and which includes software to assist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
174
0
5

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(179 citation statements)
references
References 10 publications
0
174
0
5
Order By: Relevance
“…Researchers (Joy and Luck, 1999;Daly and Horgan, 2005;Spinellis et al, 2007) have identified plagiarism issues in many perspectives. Unacknowledged copying of documents or programs is considered as an act of plagiarism.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers (Joy and Luck, 1999;Daly and Horgan, 2005;Spinellis et al, 2007) have identified plagiarism issues in many perspectives. Unacknowledged copying of documents or programs is considered as an act of plagiarism.…”
Section: Related Workmentioning
confidence: 99%
“…With rampant increment in plagiarism phenomena (Joy and Luck, 1999;Sheard and Dick, 2003) necessary efforts should be taken to provide a conducive environment that encourages students to develop their programming skills (Cogan and Gurwitz, 2009;Sani et al, (2009). Since it is so easy to copy and edit a computer program, students would find it is tempting to get involve in plagiarism activity.…”
Section: Introductionmentioning
confidence: 99%
“…Different similarity measurements such as suffix trees, string alignment, Jaccard similarity, etc., can be applied to sequences or sets of tokens. Tools that rely on tokens include Sherlock (Joy and Luck 1999), BOSS (Joy et al 2005), Sim (Gitchell and Tran 1999), YAP3 (Wise 1996), JPlag (Prechelt et al 2002), CCFinder (Kamiya et al 2002), CP-Miner (Li et al 2006), MOSS (Schleimer et al 2003), Burrows et al (2007), and the Source Code Similarity Detector System (SCSDS) (Duric and Gasevic 2013). The token-based representation is widely used in source code similarity measurement and very efficient on a scale of millions SLOC.…”
Section: Code Similarity Measurementmentioning
confidence: 99%
“…However, we can examine the reports that are produced by different plagiarism detection software when used on the same dataset. The systems used for the analysis include MOSS [6], JPlag [5] and Sherlock [3]. Every system printed a report about the same real collection, consisting of 220 undergraduate student's Java programs.…”
Section: Similarity(q F I ) = M Atchedt Okens(fmentioning
confidence: 99%
“…Modern plagiarism detectors, such as Sherlock [3], JPlag [5] and MOSS [6] use a tokenization technique to improve detection. These detectors work by pre-processing code to remove white-space and comments before converting the file into a tokenized string.…”
mentioning
confidence: 99%